The impact of video game playing on Chinese adolescents’ academic achievement: evidence from a moderated multi-mediation model - Gu, Xiaoxia; Hassan, Norlizah Che; Sulaiman, Tajularipin; Wei, Zhixia; Dong, Jingyi (Public Library of Science, 2024)
Internet access for adolescents is becoming more prevalent around the world. Although video game playing has been verified to be negatively related to adolescent academic achievement, the mechanisms underlying this relationship are also unknown. Using a nationally representative sample of adolescents from the China Education Panel Survey (2014–2015), this study aims to explore the parallel mediation roles of self-educational expectation and learning attitude in the link between video game playing and academic achievement, and whether the direct and indirect effects are moderated by parent-child relationship. The results indicate that video game playing in adolescents is both directly and indirectly related to their academic achievement, and self-educational expectation and learning attitude partially mediate this association. Moreover, the results reveal that parent-child relationship moderates the direct association between video game playing and academic achievement as well as the indirect association of video game playing on academic achievement via self-educational expectation, respectively. By showing empirical evidence for the usefulness of social cognitive theory to adolescents’ academics in the Internet Age, our research provides a supplement to existing literature.